Trade of Needs: Maslow’s Hierarchy of Needs from a Multifocal Point of View - Benders, Hans-Joachim (Digital Repository of Theses, 2025)
This research explores the cultural and generational influences on Abraham Maslow’s Hierarchy of Needs. German and Indonesian students completed a questionnaire, and statistics about Baby Boomers and Millennials were collected for the analysis and interpretation. Maslow developed his theory to describe the human behaviour. Within this original Hierarchy five Needs are defined in a fixed ranking. These are the Physiological, the Safety, the Social, the Esteem and the Self-Actualization Needs. Researchers support Maslow’s theory. The Hierarchy of Needs is used in several fields of science and helps to understand the human behaviour. There are also researchers that have another opinion and do not agree with Maslow’s idea. They see constraints and limitations in his theory. Culture is the way of life people live. It influences their daily actions, how they try to solve problems and when people take action. These characteristics can vary from culture to culture. People mostly experience just their own culture and only recognize a foreign one once they enter it. The same applies for a person’s age. People undergo different stages in their life and can have other prioritizes. All human beings have a set of inborn Needs. They are naturally given and are the trigger for our deeds. As all human beings have the same set of Needs, do people also satisfy their Needs in the same order and in the same way? People live in different cultures and period of life which take influence on their behaviour. There could be a relation between culture / age and Needs. This leads to the hypotheses that culture and age can influence the ranking of Needs and the level of satisfaction. The collected data from two different cultures and generations provides information to analysis and interpret their behaviour and motivation which ultimately lead to a final conclusion. A deeper examination of the data reveals the cultural and generational differences. These can be connected to the Hierarchy of Needs. The research confirms that the Hierarchy of Needs can vary by culture or age. It confirms that people satisfy their Needs on different degrees depending on the personal prioritization. Keywords: Baby Boomers, Culture, Generations, Germany, Indonesia, Maslow, Millennials, Motivation, Needs